Design and Fabrication of Polydimethylsiloxane Based Low Cost Microfluidic for Ultra-Fast Diagnostic Applications - Balakrishnan, SR; Hashim, U; Sahrim, M; I. Ismail; Jamaludin J.; Wan Zakiah Wan Ismail; Perumal, V; Haarindraprasad, R; Mahalingam, S (Univ Tun Hussein Onn Malaysia, 2024)
Indexed by WOS/SCOPUS/ERA